EYL TEACHER’S STRATEGIES IN CONDUCTING SPEAKING ASSESSMENTS - Novi Nurhidayah Hutagaol; Maya Oktora (Universitas Negeri Medan, 2022)
This study aimed to describe (1) what is the strategies that teacher’s use in assessing young learners’ speaking skill (2) To know the problems faced by teacher in assessing young learners’ speaking skill. Assessing speaking skills for young learners is one of the difficult tasks in language learning because young learners’ have higher activity levels and easily distracted by others. English teachers need to be competent in applying strategies in conduct speaking assessment for young learners’. The research was conducted at SD GenBi School Medan. This research used descriptive qualitative method. The subject of this research was English teacher of SD GenBi School Medan. The data were obtained through observation, and interview. The data were analyzed by qualitative data analysis technique which consists of three events, namely ; data reduction, data presentation, and make a conclusion of data. The findings showed that the teacher use various strategies when conducting the speaking assessments, namely; Picture Talks, Story-telling, Oral Presentations, Answering Open-questions, Minidialogues and role-plays, and Word Repetition Tasks. But in its, the teacher faced some problems. The problem was time limitation. Furthermore, speaking assessments strategies is very difficult to address to young learners' whereas teachers must look at young learners' ability to focus individually. And it took a lot of time.Keywords: Young Learners’, Assessments, Assessments Strategies, Speaking Skill.